2011
DOI: 10.4103/0189-6725.86062
|View full text |Cite
|
Sign up to set email alerts
|

Our experience in the management of infantile hydrocephalus: A study on thirty-five regrouped cases in Yaounde, Cameroon

Abstract: Hydrocephalus is a frequent disorder in this Cameroonian setting affecting mostly the 0-6 months age group. For early diagnosis to be made, the head circumference of neonates should be routinely measured in the labour room and followed-up in all medical visits. To avert complications following surgery, rigorous surgical procedures with effective asepsis and appropriate methods and materials for shunting should be used.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
2
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 7 publications
1
2
0
1
Order By: Relevance
“…HC secondary to post-intraventricular hemorrhage was the least common cause of HC requiring a shunt in infancy. All these trends are consistent with previous studies such as those by Mouafo Tambo et al ,[ 10 ] in which they found aqueductal stenosis in 31.43% cases.…”
Section: Discussionsupporting
confidence: 93%
“…HC secondary to post-intraventricular hemorrhage was the least common cause of HC requiring a shunt in infancy. All these trends are consistent with previous studies such as those by Mouafo Tambo et al ,[ 10 ] in which they found aqueductal stenosis in 31.43% cases.…”
Section: Discussionsupporting
confidence: 93%
“…Les taux de complications varient entre 1 et 50%, deux ans après la chirurgie [ 2 , 12 , 22 - 25 ]. Dans les séries de l´Afrique subsaharienne, les complications décrites varient entre 7% et 69% et sont liées à des causes mécaniques (11-54%) et à l´infection (7-69%) [ 6 , 13 , 23 , 24 , 26 - 28 ]. La pose de DVP est plus dangereuse dans le contexte africain que dans les pays développés en raison des complications infectieuses et du dysfonctionnement de valve [ 25 ].…”
Section: Discussionunclassified
“…In the series of sub-Saharan Africa, the described complications vary between 7% and 69% and are related to mechanical causes (obstruction and VPS system migration) (11-54%) and infection (7-69%). [ 4 28 31 35 37 39 40 44 ] Even when the VPS placement is possible, it is more dangerous in the African context than in developed countries because of the infectious complications and shunt's malfunctioning. [ 42 ] Infectious complications of VPS implantation can be reduced by implementing protocols that train staff in infection control measures related to the preoperative, operative, and postoperative period, as reported by Choux et al .,[ 6 ] being fundamental to adapt this knowledge to local reality.…”
Section: Discussionmentioning
confidence: 99%
“…A large number of children may alternatively benefit from endoscopic third ventriculostomy (ETV), which is a treatment option, without heterologous material, with a long-term lower rate of associated complications[ 17 23 39 43 ] and with a follow-up that we believe can be less frequent, thus reducing the socioeconomic impact on the families of these patients. [ 46 47 ]…”
Section: Discussionmentioning
confidence: 99%